The Effect of The VAK Learning Model (Visualization Auditory Kinestetik) on Student Motivation and Learning Outcomes on Circulatory System Material at SMA Negeri 1 Langsa - Purnama, Aufa (Jurnal Biologi Sains dan Kependidikan, 2022)
Education is a process of human effort in expanding the knowledge he has.TheVAKlearning model is a learning model(Visualization Auditory Kinesthetic)that does not only focus on 1 sensory but uses 3 sensory, namelyvisual, auditory and kinesthetic.This study aims to determine the influence of the VAKlearning model(Visualization Auditory Kinesthetic) on student motivation and learning outcomes.the population used in this study was all students of class XI MIA SMA Negeri 1Langsa, and obtained 2 classes by simple random sampling as a research sample, XI MIA 7 as a class experiment and class XI MIA 8 as a class control.The hypothesis test used in this study is the T Test(Independent Sample T Test).Based on the results of this study, learning motivation is as large astcountttable3,60 1,994with a significant level of 0.05 and research results on learning outcomes oftcountttable5,546 1,994 with a significant level of 0,05.Therefore, the hypothesis is acceptable. based on the conclusions of this study, there is an influence of the VAK learning model on student motivation and learning outcomes on circulatory system material at SMA Negeri 1Langsa